Strategi Peningkatan Keterampilan Mengajar Guru dalam Pembelajaran Tari Dolalak pada Anak Usia Dini di Kabupaten Purworejo: Perspektif Konseptual - Lambang Febrina Rih Fiarsy; Ni Kadek Aris Rahmadani (EduInovasi: Journal of Basic Educational Studies, 2025)
Learning local wisdom-based dance arts, especially Dolalak Dance, for early childhood has an important role in preserving culture and shaping children's character. However, the limited competence of teachers in the field of dance arts and cultural pedagogy is a major challenge. This article aims to examine strategies for improving teachers' teaching skills in learning Dolalak Dance through the SLR (Systematic Literature Review) method for various scientific articles that have been reviewed. The articles used in this study were six national journal articles obtained from the Google Scholar database using the Publish or Perish application. The results of the review of the six articles concluded that local culture-based training, ethnoscience integration, motor-affective approaches, collaboration with art studios, and curriculum innovation are relevant and contextual strategies to improve the teaching skills of PAUD teachers in learning Dolalak Dance.